The Effects of 1,4-Naphthoquinone (NQ) and Naphthazarin (5,8-Dihydroxy-1,4-naphthoquinone, DHNQ) Individually and in Combination on Growth and Oxidative Stress in Maize (Zea mays L.) Seedlings - Waldemar Karcz; Zbigniew Burdach; Małgorzata Rudnicka (Plants, 2023)
This study investigated the effects of 1,4-naphthoquinone (NQ) and naphthazarin (5,8-dihydroxy-1,4-naphthoquinone, DHNQ) individually and in combination, applied at low concentrations (0.1, 1, and 10 nM), on growth, hydrogen peroxide (H2O2) production, catalase activity, and lipid peroxidation in maize seedlings. It was found that NQ at 0.1 and 1 nM and DHNQ at 0.1 nM significantly stimulated the fresh weight of the aboveground parts of the seedlings (APS), while the fresh weight of the underground parts of the seedlings (UPS) was enhanced only at 0.1 nM NQ. Interestingly, DHNQ at higher concentrations (1 and 10 nM) significantly diminished the fresh weight of the APS and UPS. When NQ and DHNQ were applied together, an increase in the fresh weight of the APS at all of the concentrations studied was observed. It was also found that NQ and DHNQ individually and in combination, at all concentrations studied, decreased the H2O2 production in the aboveground and underground parts of maize seedlings. The presence of the DHNQ at higher concentrations (1 and 10 nM) triggered an increase in the catalase (CAT) activity of the UPS and APS compared to the control. However, NQ added at 1 nM decreased the CAT activity of both the UPS and APS, while 10 nM increased the CAT activity of UPS. NQ and DHNQ applied together at 0.1 and 10 nM almost completely inhibited catalase activity in the UPS and APS. The data that were obtained for lipid peroxidation, measured as the malondialdehyde (MDA) concentration, indicated that NQ and DHNQ at all concentrations studied decreased the MDA content of the UPS, while both naphthoquinones increased it in APS. The data presented here are discussed taking into account the mechanisms via which naphthoquinones interact with biological systems.